Relationship Between Humor in Advertising and Attitude Towards Ads : A Meta-Analysis - Kaur, Simranjeet; Nim, Dheeraj; Jaggi, Shamily (Indian Journal of Marketing, 2022)
Humor is anything that is funny or is intended to be funny. Humor is a fundamental social communication ingredient used profusely in advertising worldwide. Humor in advertisements makes it an excellent tool for companies and brands to lure people into liking their products. The purpose of this paper was to do a systematic review and conduct a meta-analysis of studies analyzing the relationship between humor in advertising and attitude towards the ads. We found 171 articles that mentioned humor in advertising ; 71 articles were found with studies on both humor and attitude towards the ads. After scrutiny and systematic review, only 13 studies were included in the final study. The random effect model was used for the effect size because the studies belonged to different populations. Baujat plot was used to detect the studies causing heterogeneity. It was found that there was a large amount of variance in studies included in the analysis.